OPCW Proficiency Test: A Practical Approach Also for Interlaboratory Test on Detection and Identification of Pesticides in Environmental Matrices - Leszek Konopski; Pingfeng Liu; Wuri Wuryani; Maciej Śliwakowski (The Scientific World Journal)
An overview of general strategy, standard procedures, and critical points, which may be found during carrying out an OPCW Proficiency Test concerning detection and identification of scheduled compounds relevant to Chemical Weapon Convention, has been presented. The observations have been illustrated following the case of the Eight OPCW Designated Laboratories Proficiency Test, which was performed in the OPCW Laboratory in Rijswijk in November and December 2000. Various useful hints, comments, and practical observations concerning the case study have been included as well. The same methodology and procedures may be also applied for detection, identification, and environmental analyses of pesticides and biocides, especially organophosphorus compounds.